Reduction of bioavailability and leachability of heavy metals during agitated pile composting of Salvinia natans weed of Loktak lake - W. Roshan Singh; Shashi Kumar Pankaj; Ajay S. Kalamdhad (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Composting of harvested Salvinia natans weed of Loktak lake of Manipur, India can protect the precious lake from the unwanted growth of the weeds but there is a need to assess the total amount and bioavailable forms of heavy metals and minerals of the final compost before application as a soil conditioner. Methods Studies were conducted on the transformations of the physico-chemical parameters and the total amount, bioavailable and leachable forms of heavy metals and minerals during agitated pile composting of S. natans with rice husk and cattle manure in five different combinations [trial 1 (5 S. natans: 4 cattle manure: 1 rice husk), trial 2 (6 S. natans: 3 cattle manure: 1 rice husk), trial 3 (7 S. natans: 2 cattle manure: 1 rice husk), trial 4 (8 S. natans: 1 cattle manure: 1 rice husk) and trial 5 (10 S. natans: 0 cattle manure: 0 rice husk)]. Results The highest temperature (52.2 C) was monitored in trial 2 having 30 % cattle manure during the process. Highest reduction of moisture content and volatile solid in trial 2 corroborated the temperature profile. Total concentrations of heavy metals (Zn, Cu, Mn, Fe, Ni, Pb, Cd and Cr), total concentration of nutrients (Na, K, Ca, and Mg) and the water-soluble forms of the nutrients were enhanced significantly. The water-soluble, plant-available and leachable metals decreased favorably with maximum reduction observed mostly in trial 2. The study also revealed that the total concentrations of Zn (211â254 mg/ kg), Ni (310â345 mg/kg) and Pb (805â891 mg/kg) of the final composts were higher than that of Cr (140â207 mg/ kg) but the water-soluble forms of Zn (3.6â4.7 % of total Zn), Ni (NIL) and Pb (0.7â1.0 % of total Pb) were lower than that of Cr (13.3â19.3 % of total Cr) indicating that Cr in the composts had higher toxicity potential. The leachable heavy metals were within the threshold limits prescribed for agricultural application. Conclusions Composting of S. natans biomass with appropriate proportion of cattle manure reduced the bioavailable and leachable forms of the heavy metals in the biomass.